2016
DOI: 10.1103/physrevd.93.065008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relativistic effects on satellite-based clock synchronization

Abstract: Clock synchronization between the ground and satellites is a fundamental issue in future quantum telecommunication, navigation, and global positioning systems. Here, we propose a scheme of near-Earth orbit satellitebased quantum clock synchronization with atmospheric dispersion cancellation by taking into account the spacetime background of the Earth. Two frequency entangled pulses are employed to synchronize two clocks, one at a ground station and the other at a satellite. The time discrepancy of the two cloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…The relation between anormalΩA and anormalΩB was discussed in refs. [], and can be used to calculate the relation between the frequency distributions FnormalΩK,0false(Kfalse) of the photons before and after the propagation FΩB,0(B)false(ΩBfalse)=ffalse(rBfalse)ffalse(rAfalse)4FΩA,0(A)f(rB)f(rA)ΩBFrom Equation , we can see that the effect induced by the curved spacetime of the Earth cannot be simply corrected by a linear shift of frequencies. Therefore, it may be challenging to compensate the transformation induced by the curvature in realistic implementations.…”
Section: Light Wave Packets Propagating In the Curved Spacetimementioning
confidence: 99%
See 3 more Smart Citations
“…The relation between anormalΩA and anormalΩB was discussed in refs. [], and can be used to calculate the relation between the frequency distributions FnormalΩK,0false(Kfalse) of the photons before and after the propagation FΩB,0(B)false(ΩBfalse)=ffalse(rBfalse)ffalse(rAfalse)4FΩA,0(A)f(rB)f(rA)ΩBFrom Equation , we can see that the effect induced by the curved spacetime of the Earth cannot be simply corrected by a linear shift of frequencies. Therefore, it may be challenging to compensate the transformation induced by the curvature in realistic implementations.…”
Section: Light Wave Packets Propagating In the Curved Spacetimementioning
confidence: 99%
“…Indeed, such a nonlinear gravitational effect is found to influence the fidelity of the quantum channel between Alice and Bob . It is always possible to decompose the mode a¯ received by Bob in terms of the mode a prepared by Alice and an orthogonal mode a (i.e., [a,a]=0) truea¯=Θa+1normalΘ2awhere Θ is the wave packet overlap between the distributions FΩB,0(B)false(ΩBfalse) and FΩA,0(A)false(ΩBfalse)0truenormalΘ:=0+dΩB0.16emFnormalΩB,0false(Bfalse)(normalΩB)FnormalΩA,0false(Afalse)(normalΩB)and we have Θ=1 for a perfect channel.…”
Section: Light Wave Packets Propagating In the Curved Spacetimementioning
confidence: 99%
See 2 more Smart Citations
“…It was experimentally demonstrated that the gravitational frequency shift (GFS) effects have a remarkable influence on the precision of atomic clocks for a variation of 0.33m in height [34]. In addition, relativistic effects of the Earth notably affect satellite-based quantum information processing tasks [35][36][37] and quantum clock synchronization [38]. Quantum information also plays a prominent role in the study of the thermodynamics and information loss problem [40,41] of black holes.…”
Section: Introductionmentioning
confidence: 99%